2009
DOI: 10.1111/j.1570-7458.2009.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal taste sensilla of the autumn gum moth, Mnesampela privata: morphology and electrophysiological activity

Abstract: Mnesampela privata Guenée (Lepidoptera: Geometridae: Ennominae) is a native Australian geometrid that conducts considerable host assessment prior to ovipositing on its host plants, which belong to the genus Eucalyptus. The leaves of some of their hosts are covered with a particularly thick and waxy cuticle and we have shown that epicuticular waxes influence the oviposition preferences of females. This necessitates that M. privata has evolved specific chemosensory organs to assess the identity and perhaps even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Nevertheless, because variations in amounts of primary metabolites can influence insect survival and growth, it is quite possible that an insect such as M. privata may alter the numbers of eggs laid on families of E. globulus and E. nitens depending upon the primary metabolites they encounter on leaf surfaces. Importantly, Calas et al (2009) have shown that female M. privata are capable of contact chemoreception of leafsurface primary metabolites by virtue of taste sensilla on their fifth tarsomeres. One pair of these sensilla exhibits notably larger responses to the amino acids alanine and serine than the other sensilla.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because variations in amounts of primary metabolites can influence insect survival and growth, it is quite possible that an insect such as M. privata may alter the numbers of eggs laid on families of E. globulus and E. nitens depending upon the primary metabolites they encounter on leaf surfaces. Importantly, Calas et al (2009) have shown that female M. privata are capable of contact chemoreception of leafsurface primary metabolites by virtue of taste sensilla on their fifth tarsomeres. One pair of these sensilla exhibits notably larger responses to the amino acids alanine and serine than the other sensilla.…”
Section: Discussionmentioning
confidence: 99%
“…In Papilionidae (such as Papilio xuthus , Heliconius melpomene and Papilio polytes ), female butterflies perceive oviposition stimulant by the chemosensilla located on the ventral side of their foreleg tarsus and further determine the suitable feeding plant for larvae [ 10 12 ]. In other lepidopteran species (such as Mnesampela privata , Helicoverpa armigera and Heliothis virescens ) ( Fig 1 ), tarsal chemosensilla of the prothoracic legs are sensitive to some salts, sugars and amino acids, which indicates a role in the assessment of food materials [ 13 15 ]. Legs of Drosphila , functioning as gustatory organ and being responsible for tastant recognition, contain several taste sensilla and make the initial contact with potential food resources [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ramaswamy (Ramaswamy, 1987) responded to these three sugars and the amino acids, Ala, Phe, Leu and Lys. A recent study by Calas et al (Calas et al, 2009) showed that tarsal chemosensilla responded to sucrose, glucose, fructose and the amino acids, Ala and Ser. We studied the full set of chemosensilla on the fifth tarsomere of H. armigera stimulated with four sugars, one sugar alcohol and 20 amino acids, and we found that the response spectra of some tarsal chemosensilla were broad and that of others more narrow.…”
Section: Electrophysiological Response Spectra Of Tarsal Chemosensillamentioning
confidence: 99%
“…The contact chemoreceptive function of tarsal chemosensilla in detecting sugars and amino acids has been demonstrated in four noctuid species by Blaney and Simmonds (Blaney and Simmonds, 1990). A recent study showed that tarsal taste sensilla of Mnesampela privata were sensitive to some salts, sugars and amino acids (Calas et al, 2009). These results indicated that tarsal sensilla played a role in the assessment of food materials.…”
Section: Introductionmentioning
confidence: 99%